SOME ASPECTS OF THE USE OF SOCIO-CULTURAL TOOLS IN TEACHING FOREIGN LANGUAGE (Scientific journal of the Fergana State University, 2023)
The article gives an idea of the techniques for achieving the productivity of foreign learning activities. According to the author, a foreign learner should consciously master the phonetics, morphology and linguistics of the studied foreign language and be able to use them in communication.